THEORETICAL BASIS OF FORMING PROFESSIONAL COMPETENCIES OF FUTURE FOREIGN LANGUAGE TEACHERS USING DIGITAL TECHNOLOGIES - Saydazimova, Durdona (Educational Research in Universal Sciences, 2023)
The article is devoted to the willingness and ability to solve problems, navigate the limitless flow of information, find the right answers from the alternatives offered by life, develop the human resources inherent in nature in working on the individuality of each individual, show true interest in what you love, be interested in the latest methodological advances in science, that will lay everything foundation of the education of the future.